2017
DOI: 10.5267/j.msl.2017.8.006
|View full text |Cite
|
Sign up to set email alerts
|

Critical success factors model developing for sustainable Kaizen implementation in manufactur-ing industry in Ethiopia

Abstract: The purpose of the research is to identify critical success factors and model developing for sustaining kaizen implementation. Peacock shoe is one of the manufacturing industries in Ethiopia facing challenges on sustaining. The methodology followed is factor analysis and empirically testing hypothesis. A database was designed using SPSS version 20. The survey was validated using statistical validation using the Cronbach alpha index; the result is 0.908. The KMO index value was obtained for the 32 items and had… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(21 citation statements)
references
References 8 publications
2
14
0
1
Order By: Relevance
“…Different scholars also identified Kaizen practices as independent variables: leadership or top management support (Shafiq et al , 2019; Jong et al , 2019; Rawashdeh, 2018; Baye and Raju, 2016; Jalu, 2015; Beshah and Kitaw, 2014); Customer focus (Jong et al , 2019; Rawashdeh, 2018; Baye and Raju, 2016; Beshah and Kitaw, 2014); People management (Shafiq et al , 2019; Jong et al , 2019; Rawashdeh, 2018; Baye and Raju, 2016); Process management (Shafiq et al , 2019; Jong et al , 2019; Rawashdeh, 2018; Baye and Raju, 2016; Beshah and Kitaw, 2014); Continuous improvement (Rawashdeh, 2018; Baye and Raju, 2016); Product design (Psomas et al , 2014); Supplier quality management (Rawashdeh, 2018; Baye and Raju, 2016); Strategy (policy, strategic planning) (Shafiq et al , 2019; Jong et al , 2019; Rawashdeh, 2018); Resources including partnership (Shafiq et al , 2019; Beshah and Kitaw, 2014); Measurement, analysis and knowledge management (Jong et al , 2019; Rawashdeh, 2018); Kaizen tools and techniques (Jalu, 2015). Moreover, other preceding studies also identified Kaizen practices as CSFs: leadership (Janjić et al , 2019; Hailu et al , 2017b); Top management policy, commitment, support (Kumar, 2019; Lina and Ullah, 2019; Todorovic et al , 2019; Abdulmouti, 2018; Hailu et al , 2017b); process control (2017b); Culture of effective and flexible suggestion system (Kumar, 2019; Abdulmouti, 2018; Hailu et al , 2017b); the use of problem-solving approach (Kumar, 2019; Abdulmouti, 2018; Khanna et al , 2017a, b; Amrutkar and Kamalja, 2017) and Supportive organization structure (Kumar, 2019; Janjić et al , 2019); employee's attitude (Hailu et al , 2017b); employee's and management involvement, team dynamics (good presentation and communication skills), recognition (Janjić et al , 2019; Abdulmouti, 2018; Hailu et al , 2017b); good management–employee relationship and train employees (T...…”
Section: Literature Reviewmentioning
confidence: 82%
See 4 more Smart Citations
“…Different scholars also identified Kaizen practices as independent variables: leadership or top management support (Shafiq et al , 2019; Jong et al , 2019; Rawashdeh, 2018; Baye and Raju, 2016; Jalu, 2015; Beshah and Kitaw, 2014); Customer focus (Jong et al , 2019; Rawashdeh, 2018; Baye and Raju, 2016; Beshah and Kitaw, 2014); People management (Shafiq et al , 2019; Jong et al , 2019; Rawashdeh, 2018; Baye and Raju, 2016); Process management (Shafiq et al , 2019; Jong et al , 2019; Rawashdeh, 2018; Baye and Raju, 2016; Beshah and Kitaw, 2014); Continuous improvement (Rawashdeh, 2018; Baye and Raju, 2016); Product design (Psomas et al , 2014); Supplier quality management (Rawashdeh, 2018; Baye and Raju, 2016); Strategy (policy, strategic planning) (Shafiq et al , 2019; Jong et al , 2019; Rawashdeh, 2018); Resources including partnership (Shafiq et al , 2019; Beshah and Kitaw, 2014); Measurement, analysis and knowledge management (Jong et al , 2019; Rawashdeh, 2018); Kaizen tools and techniques (Jalu, 2015). Moreover, other preceding studies also identified Kaizen practices as CSFs: leadership (Janjić et al , 2019; Hailu et al , 2017b); Top management policy, commitment, support (Kumar, 2019; Lina and Ullah, 2019; Todorovic et al , 2019; Abdulmouti, 2018; Hailu et al , 2017b); process control (2017b); Culture of effective and flexible suggestion system (Kumar, 2019; Abdulmouti, 2018; Hailu et al , 2017b); the use of problem-solving approach (Kumar, 2019; Abdulmouti, 2018; Khanna et al , 2017a, b; Amrutkar and Kamalja, 2017) and Supportive organization structure (Kumar, 2019; Janjić et al , 2019); employee's attitude (Hailu et al , 2017b); employee's and management involvement, team dynamics (good presentation and communication skills), recognition (Janjić et al , 2019; Abdulmouti, 2018; Hailu et al , 2017b); good management–employee relationship and train employees (T...…”
Section: Literature Reviewmentioning
confidence: 82%
“…This study also used seven drivers of Kaizen philosophy practice identified by Hailu et al (2020) as social factors: leadership and people; technical factors: process, strategy, partnership, resource and problem-solving approach as technical factors to explore the factors practiced by Ethiopian chemical manufacturing companies. Moreover, this study also used organizational effect measures as stated earlier and identified by Lina and Ullah (2019), Hailu et al (2017b, 2015), Desta (2014) and Imai (1986) to explore the confirmed various positive effects achieved during practice of Kaizen philosophy including both qualitative and quantitative (monetary and nonmonetary) results. Therefore, from the aforementioned literature, this research developed a research framework (Figure 1), which related the independent variable of Kaizen practices (structured implementation framework, social, technical factors) to dependent variable of organizational effect (quantitative – monetary and nonmonetary and qualitative results) (see Figure 2).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations